Pendampingan keberlanjutan kompetensi digital guru sebagai upaya meningkatkan kualitas pembelajaran di sekolah dasar - Nurdinah Hanifah; Dadan Djuanda; Riana Irawati (Universitas PGRI Madiun, 2026)
Elementary school teachers' digital competence often improves rapidly immediately after training, but tends to decline in sustainability once ongoing mentoring is no longer provided. This community service activity aims to accompany elementary school teachers so that their digital competence can be applied consistently and independently in daily instruction, and to evaluate its relationship with the perceived quality of learning. The activity was carried out through socialization, digital competence reinforcement training, classroom implementation mentoring, and a sustainability evaluation using a questionnaire administered to 22 partner elementary school teachers. The evaluation questionnaire consisted of 27 statements grouped into four dimensions: implementation autonomy, sustainability of impact, planning and management of digital learning, and quality of learning outcomes. The evaluation results show that all four dimensions fall within the moderate-to-high category, with mean scores of 2.96 for autonomy, 3.13 for sustainability of impact, 3.30 for planning and management, and 3.10 for learning outcome quality (on a 1-5 scale). Correlation analysis revealed a strong and significant positive relationship between the overall sustainability of teachers' digital competence and the quality of learning (r = 0.81; p 0.001), indicating that the more sustainable and autonomous teachers' application of digital competence, the higher the perceived quality of classroom learning. Technical autonomy aspects, such as resolving technical obstacles independently and developing media variations on one's own initiative, were identified as areas still requiring further mentoring. This activity recommends a sustainable post-training mentoring model as a strategy to strengthen the quality of elementary school learning, in line with the spirit of deep learning and the use of technology, including artificial intelligence, to support quality education.